2016
DOI: 10.1007/s15010-016-0955-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of transrenal DNA for the diagnosis of pulmonary tuberculosis and treatment monitoring

Abstract: The detection of M. tuberculosis trDNA from urine specimen is a promising method for the diagnosis tuberculosis. The assay may be a candidate diagnostic tool for patients with paucibacillary and extrapulmonary disease, as method to assess treatment responses and could be helpful to diagnose tuberculosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 26 publications
5
44
0
4
Order By: Relevance
“…Molecular tests such as the GeneXpert (Cepheid, USA) or the line-probe assays (Hain Life Sciences, Nehren, Germany) are commercially available as rapid diagnostic methods that permit drug-resistance prediction for important first-and second-line drugs (76,77). As an alternative, transrenal DNA, and lipoarabinomannan (LAM) detection in urine have been described to diagnose active tuberculosis in people living with HIV (78)(79)(80). Screening for tuberculosis with a LAM urine assay in African people living with HIV and low CD4 count lead to a significant decrease in mortality (81).…”
Section: Iv: Biomarker Based Treatment Decisionsmentioning
confidence: 99%
“…Molecular tests such as the GeneXpert (Cepheid, USA) or the line-probe assays (Hain Life Sciences, Nehren, Germany) are commercially available as rapid diagnostic methods that permit drug-resistance prediction for important first-and second-line drugs (76,77). As an alternative, transrenal DNA, and lipoarabinomannan (LAM) detection in urine have been described to diagnose active tuberculosis in people living with HIV (78)(79)(80). Screening for tuberculosis with a LAM urine assay in African people living with HIV and low CD4 count lead to a significant decrease in mortality (81).…”
Section: Iv: Biomarker Based Treatment Decisionsmentioning
confidence: 99%
“…However, since this marker yields positive results before treatment initiation where higher overall bacterial loads are to be found it may not be suitable to serve during late time‐points during therapy when most bacteria are already killed. Specific mycobacterial PCRs from sputum and urine were analyzed to serve as markers for therapy response . Although mycobacterial DNA from these compartments were identified even late after therapy initiation, the pathogen's viability cannot be determined, which questions these results' relevance for the clinic.…”
Section: Biomarker Guided Treatment Decisionsmentioning
confidence: 99%
“…Studies of Aspergillus PCR have demonstrated that Aspergillus DNA in serum remains relatively stable for the first week after treatment, and clearance by 2-3 weeks may be associated with favorable treatment outcomes (Imbert et al, 2016). Furthermore, in a study of urine cfDNA for tuberculosis, pathogen cfDNA increased with treatment (Labugger I et al, 2017). Further investigation will be needed to understand the potentially unique biologic variances of different organisms and to better understand the effects of antifungal treatment on the dynamics of pathogen cell-free DNA to interpret the performance of plasma NGS in patients with invasive fungal infections.…”
Section: Non-invasive Biomarkers For Ifi Including Thementioning
confidence: 99%